2016
DOI: 10.1007/s11682-016-9557-y
|View full text |Cite
|
Sign up to set email alerts
|

Neural response patterns in spider, blood-injection-injury and social fearful individuals: new insights from a simultaneous EEG/ECG–fMRI study

Abstract: In the present simultaneous EEG/ECG-fMRI study we compared the temporal and spatial characteristics of the brain responses and the cardiac activity during fear picture processing between spider, blood-injection-injury (BII) and social fearful as well as healthy (non-fearful) volunteers. All participants were presented with two neutral and six fear-related blocks of pictures: two social, two spider and two blood/injection fear blocks. In a social fear block neutral images were occasionally interspersed with pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 72 publications
2
16
0
Order By: Relevance
“…The 31 studies included 564 patients with SP and 485 HC (Brinkmann, Poller, Herrmann, Miltner, & Straube, ; Britton et al, ; Caseras, Giampietro, et al, ; Caseras, Mataix‐Cols, et al, ; Dilger et al, ; Goossens, Schruers, Peeters, Griez, & Sunaert, a; Goossens et al, 2007b Halsband & Wolf, ; Hermann et al, ; Hilbert, Evens, Maslowski, Wittchen, & Lueken, ; Killgore et al, ; Lipka et al, ; Lipka, Miltner, & Straube, ; Lueken et al, , ; Michalowski et al, ; Munsterkotter et al, ; Scharmuller et al, ; Schienle et al, ; Schienle, Schafer, Walter, Stark, & Vaitl, ; Schienle, Scharmuller, Leutgeb, Schafer, & Stark, ; Schweckendiek et al, ; Straube, Glauer, et al, ; Straube, Lipka, Sauer, Mothes‐Lasch, & Miltner, ; Straube et al, ; Straube, Mentzel, & Miltner, , ; Wendt, Lotze, Weike, Hosten, & Hamm, ; Wiemer et al, ; Wright et al, ; Zilverstand, Sorger, Kaemingk, & Goebel, ). In six studies, two different subtypes of phobias were considered, with the most studied (24 out of 31) subtype being spider phobia; dental phobia was evaluated in six studies, whereas small animal and blood/injection subtypes in four and three studies, respectively (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 31 studies included 564 patients with SP and 485 HC (Brinkmann, Poller, Herrmann, Miltner, & Straube, ; Britton et al, ; Caseras, Giampietro, et al, ; Caseras, Mataix‐Cols, et al, ; Dilger et al, ; Goossens, Schruers, Peeters, Griez, & Sunaert, a; Goossens et al, 2007b Halsband & Wolf, ; Hermann et al, ; Hilbert, Evens, Maslowski, Wittchen, & Lueken, ; Killgore et al, ; Lipka et al, ; Lipka, Miltner, & Straube, ; Lueken et al, , ; Michalowski et al, ; Munsterkotter et al, ; Scharmuller et al, ; Schienle et al, ; Schienle, Schafer, Walter, Stark, & Vaitl, ; Schienle, Scharmuller, Leutgeb, Schafer, & Stark, ; Schweckendiek et al, ; Straube, Glauer, et al, ; Straube, Lipka, Sauer, Mothes‐Lasch, & Miltner, ; Straube et al, ; Straube, Mentzel, & Miltner, , ; Wendt, Lotze, Weike, Hosten, & Hamm, ; Wiemer et al, ; Wright et al, ; Zilverstand, Sorger, Kaemingk, & Goebel, ). In six studies, two different subtypes of phobias were considered, with the most studied (24 out of 31) subtype being spider phobia; dental phobia was evaluated in six studies, whereas small animal and blood/injection subtypes in four and three studies, respectively (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The inferior frontal gyrus (IFG) was found more active in individuals with phobias, and several studies contribute to the ALE cluster encompassing this region (Supporting Information Table S4). The pattern of activity of this brain area has been linked to different presentation modalities of phobic stimuli (e.g., words; Straube et al, ) and to different subtypes of phobias (e.g., spider phobia, blood, injury and injection phobia; Caseras, Giampietro, et al, ; Caseras, Mataix‐Cols, et al, ; Michalowski et al, ). It has been suggested that an increment in hemodynamic activity in the IFG and, more generally, in the prefrontal cortex, may be related to the reduction of emotional appraisal abilities in patients with specific phobia (Caseras, Giampietro, et al, ; Michalowski et al, ; Straube et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results with respect to ERPs are well in line with the existing literature. In previous studies, elevated P300 and LPP amplitudes have been observed in PP when confronted with phobic stimuli 8 , 9 , 11 , 12 . It has been suggested that the effect of psychotherapy might not influence early ERPs of attention allocation and attentional significance, but rather late potentials of cognitive control.…”
Section: Discussionmentioning
confidence: 76%
“…With respect to spider phobia, combined measurements of fMRI and EEG have been analyzed in a study of Michalowski et al, in which neural response patterns in spider phobic, blood-injection injury and socially fearful individuals in response to fear-specific, as well as neutral stimuli, were investigated 8 . Fear-specific stimuli elicited larger LPP’s than neutral pictures, especially in the respective fearful individuals.…”
Section: Introductionmentioning
confidence: 99%